Evidential Markers in German Scientific and Popular Science Discourse: Comparative Analysis - E. V. Bodnaruk; T. N. Astakhova (Научный диалог)
The purpose of this article is a comparative analysis of evidential markers in German-language texts of scientific and popular science discourse. The novelty of the study lies in the fact that today there are no scientific works devoted to comparing the means of expressing evidentiality in these types of discourse. Evidence markers contain a link to the source of the information. The researchers note that indicating the source of information increases the degree of reliability of the reported information. One of the main characteristics of scientific and popular science discourse is intertextuality, which is expressed with the help of evidential markers that vary depending on the discourse. The material of the study was 5 texts (299 mentions of the source of information) of scientific and 28 texts (281 mentions of the source of information) of popular science discourse in German, dedicated to the problems of the Arctic. As a result of the study, it was found that statements with evidential meanings “direct evidentiality” and “citation” are more common in scientific discourse than in popular science. At the same time, full citations are less common in scientific texts than in popular science ones. The meaning “rumors” as well as fragmentary quoting are rather rare in both discourses. The lowest frequency was found by the value “inferentiality”, fixed only in the texts of popular science discourse.